Computational models for patient-specific analysis of pulmonary vascular disease. (2015) - Clark, Alys; Burrowes, Kelly; Tawhai, Merryn
Abstract : It is becoming increasingly apparent that personalized therapies are key to successful management of pulmonary vascular disease, but this cannot be achieved without an integrated approach to investigating the condition and an individual's response to therapy. Computational models provide a means to link investigations across the spectrum from cellular mechanisms to potential improvements in pulmonary vascular function over the course of a therapeutic strategy. Here we describe some of the computational tools that will be required for this purpose.